2015
DOI: 10.1039/c4ra11672k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sr substituted La2−xSrxNiO4+δ (x = 0, 0.2, 0.4, 0.6, and 0.8) on oxygen stoichiometry and oxygen transport properties

Abstract: Effects of Sr substitution in La 2−x Sr x NiO 4+δ (x = 0.2, 0.4, 0.6, and 0.8) on the oxygen stoichiometry, phase and transport properties were studied. Mixed effects between reduction of oxygen excess and increasing valence of Ni were found as charge compensation mechanisms. Highest oxygen diffusivity found at the minimum Sr substitution x=0.2 with an unusual increase observed when the x = 0.8. ARTICLE This journal isStoichiometry and oxygen diffusion properties of La 2−x Sr x NiO 4±δ with x = 0.2, 0.4, 0.6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
(141 reference statements)
1
31
0
Order By: Relevance
“…La-based R-P-1 oxides Substitution of La 3+ with a larger cation, such as Sr 2+ , leads to variations in oxygen stoichiometry that consequently affects the oxygen transport and exchange properties. [92] [31], D [21], E [25], F [30], G [56], H [54], I [93], La 1.9 Sr 0.1 NiO 4+δ ( I: [93], D: [21]), and La 1.8 Sr 0.2 NiO 4+δ (J: [40], I: [93]). Figure 4b (for La 2 NiO 4+δ obtained from the same report) are compared, [31] the values for the activation energies for the former two are close to one another, while the latter is significantly lower.…”
Section: Effect Of A-site Substitution On R-p-1 Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…La-based R-P-1 oxides Substitution of La 3+ with a larger cation, such as Sr 2+ , leads to variations in oxygen stoichiometry that consequently affects the oxygen transport and exchange properties. [92] [31], D [21], E [25], F [30], G [56], H [54], I [93], La 1.9 Sr 0.1 NiO 4+δ ( I: [93], D: [21]), and La 1.8 Sr 0.2 NiO 4+δ (J: [40], I: [93]). Figure 4b (for La 2 NiO 4+δ obtained from the same report) are compared, [31] the values for the activation energies for the former two are close to one another, while the latter is significantly lower.…”
Section: Effect Of A-site Substitution On R-p-1 Oxidesmentioning
confidence: 99%
“…[2,5,[25][26][27][28][29] The R-P phases of the first series (n = 1) with the general formula A 2 BO 4+δ are among the most studied for high temperature electrocatalytic/catalytic reactions, due to their stability and highly mobile nature of the hyperstoichiometric oxygen (δ) in their structure. [30][31][32][33][34] The hyperstoichiometric oxygen is accommodated by the oxygen interstitial sites in between adjacent rock-salt layers [21,[35][36][37] and charge compensated by the B-site transition metal, which exists in a mixed valence state [25,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, recently an increase of D* has been observed for compositions with high amount of Sr (x ¼ 0.8). 19 With the aim to improve the chemical stability in oxygen, high-temperature electrical conductivity and electrocatalytic activity of R 2 NiO 4+d for oxygen reduction in the present work we introduced Co 3+ cations in Pr 2 NiO 4+d . This was performed by the simultaneous replacement of the equal amounts of Pr and Ni cations by Sr and Co, respectively, according to the chemical formula Pr 2Àx Sr x Ni 1Àx Co x O 4AEd (x ¼ 0.25; 0.5; 0.75; 1.0).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of acceptors into the lattice, achieved via substitution of the La site with an alkaline earth, can drive the stoichiometry of the material into oxygen deficiency, because the charge compensation of the Sr = La defects can lead either to electron holes or to oxygen vacancies [26]. Although this general result was confirmed by several authors with model simulations [27][28][29], in the case of the La 2-x Sr x NiO 4+d series, Inprasit et al [30] reported a reduction of the oxygen diffusion coefficient with the increase of Sr doping amount. In addition, also doped nickelate electrodes maintain a considerable reactivity with YSZ and Ce-based electrolytes, probably due to the tendency of the small Ni ion to migrate inside the electrolyte lattice [31,32].…”
Section: Introductionmentioning
confidence: 99%